2017
DOI: 10.17533/udea.rccp.v30n2a07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aloe vera and vitamin E supplementation on the immune response of broilers

Abstract: Background: herbs are among the feed supplements under investigation that could replace antibiotics to improve humoral and cellular immune response in birds. Objective: this study evaluated the potential of Aloe vera (Aloe barbadensis Miller) and vitamin E as immunostimulants on humoral and cellular immune responses in broilers. Methods: broilers were randomly assigned to three dietary treatments: a negative control (basal diet + with no additive), basal diet + 1% Aloe vera gel in drinking water, and basal die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this study, VH and VH:CD improved in all segments of the small intestine in both the microencapsulated IgY and antibiotic groups. Previous studies have demonstrated that IgY and antibiotic addition to the diets can improve the development of broiler intestinal villi [ 24 , 35 ]. Moreover, the significant effect of microencapsulated IgY over non-microencapsulated IgY in this experiment may be due to the denaturation of non-microencapsulated IgY in the acidic environment of the stomach and its degradation by protein hydrolases present in the stomach and small intestine [ 14 ], leading to the increased digestibility of IgY.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, VH and VH:CD improved in all segments of the small intestine in both the microencapsulated IgY and antibiotic groups. Previous studies have demonstrated that IgY and antibiotic addition to the diets can improve the development of broiler intestinal villi [ 24 , 35 ]. Moreover, the significant effect of microencapsulated IgY over non-microencapsulated IgY in this experiment may be due to the denaturation of non-microencapsulated IgY in the acidic environment of the stomach and its degradation by protein hydrolases present in the stomach and small intestine [ 14 ], leading to the increased digestibility of IgY.…”
Section: Discussionmentioning
confidence: 99%
“…In response to feeding 0.1% or 0.2% whole plant powder in feed, increased antibody titers against the New Castle virus (NDV) were discovered in 42-day-old broilers [82]. Birds receiving 1% Aloe vera gel in their drinking water exhibited better antibody titres against sheep red blood cells (SRBCs) and NDV, as well as a stronger reaction to a phytohemagglutinin-P (PHA-P) injection, as compared to a control group, according to research by Darabighane et al [112]. In broiler chicks (1 to 42 days of age), diets supplemented with 2% Aloe vera gel increased the cellular immunological response to PHA-P injections compared to a control group [84].…”
Section: Immunomodulatory and Antimicrobial Effectsmentioning
confidence: 99%